Modification of the indirect haemagglutination test for amoebiasis - Krupp, Iris M. (1969)
Optimal conditions for carrying out the indirect haemagglutination test with sheep erythrocytes were studied using the microtitre system. The age of the erythrocytes, concentration of reagents, time and temperature of tanning, sensitization, and incubation are described with reference to replication of titres. Sera from patients with amoebic colitis were used to evaluate the test conditions.